Cyclic-tearing behaviour and J–R curves of Indian NPP pipes under displacement-controlled cyclic loading. (August 2015) - Gupta, Suneel K.; Bhasin, V.; Chattopadhyay, J.; Ghosh, A.K.; Singh, R.K.
Abstract: Currently the ductile fracture assessment of cracked pipes, under earthquake loading, is based on the monotonic J – R curve where the earthquake load is considered as a one-time applied load monotonically increasing to its maximum magnitude. The cyclic nature of earthquake load and associated cyclic-tearing damage (or cyclic J – R curve) is not explicitly considered. A series of cyclic-tearing and monotonic fracture tests is performed on circumferential through-wall-cracked pipes and pipe welds (five material categories) which are used in Indian Nuclear Power Plants (NPPs) piping system. The fracture behaviour of these pipes under cyclic loading vis-à-vis monotonic loading has been studied. The cyclic J – R curves of all material categories are significantly lower than the monotonic J – R curves and found strongly dependent on the applied load-history. Hence, cyclic J – R curve shall be evaluated for the load-history which is consistent with plant site (anticipated seismic loading), piping system layout and the crack location. The maximum moment observed during cyclic loading test is lower by a small to moderate amount than that obtained in the monotonic fracture tests on identical pipe. A relation has been obtained for cracked pipes which assesses if large crack growth/tearing would take place under displacement-controlled cyclic loading. Highlights: Cyclic/monotonic fracture pipe tests were conducted to understand cyclic fracture. Pipe fracture behaviour under displacement controlled cyclic loading studied. Cyclic J-R evaluated on 5 different material categories of Indian NPPs pipes. Relation developed to assesses if the cyclic loading cause large crack growth.